The Implementation Of Inquiry-Based Learning In Teaching Writing At The second Year pf SMPN I Nogosari Boyolali - TRIANASARI, TRIANASARI (2012)
This research aims at describing the implementation of inquiry-based learning in teaching writing at the second year of SMPN 1 Nogosari Boyolali. It is conducted to know the implementation of inquiry-based learning in teaching writing and the problems faced by the teacher in implementing the method at the second year of SMPN 1 Nogosari Boyolali. The writer gets the data of this research from event, informant, and document. The techniques of collecting data are the observation, interview and documentation in teaching learning process especially in teaching writing to clarify the implementation of inquiry-based learning and problem faced by the teacher implementing the method. The result of the analysis shows that: 1). the implementation of inquirybased learning in teaching writing at second year of SMPN 1 Nogosari consists of three stages namely, exploration, elaboration and confirmation. The implementation of method is less complete because the activities in standard process is not implemented in teaching writing process fully. 2). The problems faced by teacher implementing the method are lack of knowledge about inquirybased learning and how to implement the method, class management, limited time, and lack of teaching media.